Responses of Arabica coffee (Coffea arabica L. var. Catuaí) cell suspensions to chemically induced mutagenesis and salinity stress under in vitro culture conditions - Gatica Arias, Andrés Mauricio (2018)
Crop improvement of Coffea arabica L. (coffee) via mutagenesis could accelerate breeding programs; thus, the present study aimed to develop an in vitro protocol using the chemical mutagens sodium azide (NaN3) and ethyl methanesulfonate (EMS) on embryogenic cell suspensions of Arabica coffee variety Catuaí and, subsequently, to evaluate the responses of the resulting mutagenized tissues to salinity stress. Embryogenic suspension cultures were incubated with 0.0, 2.5, 5.0, or 10.0 mM NaN3 or 0.0, 185.2, 370.5, or 741.0 mM EMS. As the concentration of NaN3 or EMS increased, the survival of embryogenic suspension cultures decreased compared to controls. The median lethal dose (LD50) for NaN3 was 5 mM for 15 min and for EMS it was 185.2 mM for 120 min. Embryogenic suspension cultures treated with NaN3 or EMS were cultured on selective medium supplemented with 0, 50, 100, 150, 250, or 300 mM NaCl showed that 50 mM NaCl could be used as selection pressure. Plantlet growth and total amino acid content were affected by NaCl stress; some mutants had longer shoots and higher amino acid content than controls. Random amplified polymorphic DNA (RAPD) analysis was performed to determine whether the NaN3 or EMS treatments could induce genetic variability and resulted in identifiable polymorphic markers. A total of 18 10-mer primers were used to amplify genomic DNA of putative mutant and non-mutant arabica coffee embryogenic cultures and produced 50 scorable bands, of which 22% were polymorphic.